Karakteristik Serat Kulit Waru yang Disusun Laminasi Bermatrik Polyester dengan Orientasi Serat (450,500,550) terhadap Sifat Fisis dan Mekanis - Hendrajati, Dhedhi; , Ir. Bibit Sugito, MT; , Dwi Anggono, ST. M.Eng. Ph.D (2016)
Research hibiscus bark fiber composite rod is intended to describe the physical and mechanical properties of skin stem hibiscus fiber composites due to variation of the angle and macro photographs describe fiber composite skin stem hibiscus after testing the tensile and impact testing due to variations in the angle. The method to do that is to alkalization hibiscus fiber skin by soaking KMnO4 5% per 1 liter of distilled water for 2 hours. The test object is made by Hand Lay-up method, the ratio of 30% fiber, fiber orientation [-450 / 450]; [- 500/500]; [- 550/550]. using polyester resin series BQTN 157. The mechanical properties obtained are of a tensile testing using standard ASTM D3039-07 and ASTM impact testing using standard D256-03 with the variation of the angle of 450, 500, 550, as well as describe the tensile strength, impact the price and composite macro photo polyester fiber trunk hibiscus skin due to variation of the angle. The results of the tensile test composites prepared symmetry [-450 / 450], [- 500/500], [- 550/550] contained in the maximum tensile strength of composite with 450 test corner, where the strength of its increase in the amount of 42.340 N / mm2 more greater than the composite with a test corner 500, and 550. While the Izod impact testing of composites prepared symmetry [-450 / 450], [- 500/500], [- 550/550] where the smaller the angle, the greater the test 450 energy is absorbed and the price impact. At the macro image tensile test specimens fault structure composite bumpy and irregular. At an angle of 550 trials going on the enlargement process void and broken fiber is very dominating. While the macro image Izod impact testing results of composite fault structure at 450 test specimens seen that the pull-out of fiber.